PERLINDUNGAN HUKUM TERHADAP DATA REKAM MEDIS PASIEN DALAM ERA DIGITALISASI LAYANAN KESEHATAN DI INDONESIA - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2026)
The digitalisation of healthcare services in Indonesia has driven the use of electronic health records as part of efforts to improve efficiency, data integration and the quality of care. However, this development has also raised serious legal issues, particularly regarding the protection of patients’ personal and sensitive medical records. This study aims to analyse the legal protection of patients’ medical records in the era of healthcare digitalisation in Indonesia, examine the challenges and weaknesses of existing regulations, and review efforts to strengthen such data protection. This study employs a literature review using a normative legal approach through the analysis of legislation, academic journals, and relevant literature. The findings indicate that Indonesia already possesses a sufficiently robust legal framework through Law No. 27 of 2022 on the Protection of Personal Data, Law No. 17 of 2023 on Health, and Minister of Health Regulation No. 24 of 2022 on Medical Records. However, implementation still faces challenges in the form of regulatory harmonisation, digital infrastructure readiness, low data security literacy, and sub-optimal oversight. Therefore, there is a need to strengthen technical regulations, enhance human resource capacity, and ensure consistent law enforcement so that the protection of patients’ medical records can function effectively within the digital healthcare system.